Synthesis and Antioxidant Activities of Some New 4-(4-Hydroxybenzylidenamino)-4,5- dihydro-1H-1,2,4-triazol-5-one Derivatives with Their Acidic Properties - Yuksek, Haydar; Kucuk, Murat; Alkan, Muzaffer; Bahceci, Sule; Kolayli, Sevgi; Ocak, Zafer; Ocak, Ummuhan; Sahinbas, Esra; Ocak, Mirac (Asian Journal of Chemistry, 2010)
Fourteen new compounds having 4,5-dihydro-1H-1,2,4-triazol-5-one ring, namely six new 3-alkyl(aryl)-4-(4-hydroxybenzylidenamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones (3), four new 1-acetyl-3-alkyl(aryl)-4-(4-acetyloxybenzylidenamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones (4), two new 1-methyl-3-alkyl-4-(4-methoxybenzylidenamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones (5) and two new 3-alkyl(aryl)-4-[4-(p-tolylsulfonyl)-oxybenzylidenamino]-4,5-dihydro-1H-1,2,4-triazol-5-ones (6), were syn- thesized. The structures of the newly synthesized compounds were determined by elemental analysis as well as IR, 1H NMR, 13C NMR and UV spectral data and their antioxidant activities, except compounds 3e and 4f, were investigated. In addition, compounds 3a-f were titrated potentiometrically with tetrabutylammonium hydroxide in three non-aqueous solvents such as isopropyl alcohol, t-butyl alcohol and N,N-dimethyl formamide. The half-neutralization potential values and the corresponding pKa values were determined for all the cases.